Theoretical notes for a LGBTQIA+ history: a queer alternative for the essentialist/constructionist controversy - Rocha , Cássio Bruno de Araujo (Revista de História, 2023)
This paper proposes an LGBTQIA+ history that can evade the controversy between essentialists’ and constructionists’ conceptions of sexuality. To do so, the text reviews the assumptions, concepts, limits, and contradictions of each one, detailing the varying types of history that each evoke. Following, it presents a queer historiographical alternative, whose center is the deconstruction of the heterosexual/homosexual binary, denouncing how the essentialist and the constructionist views act to sustain the sexual and gender binary. Finally, the paper questions itself about the heuristic value of the anachronism inherent to the proposed approach, problematizing how some past categories of homoeroticism may remain as a non-resolved presence on a given historical present.